Co-digestion of pig slaughterhouse waste with sewage sludge. (June 2015) - Borowski, Sebastian; Kubacki, Przemysław
Highlights: Meat tissue gave the highest methane yield of 976 dm 3 /kg VS. The biomethane potential of sewage sludge was 370 dm 3 /kg VS. The co-digestion of SHW with sewage sludge yielded 600 dm 3  CH4 /kg VS. A slight inhibition of methanogenesis was observed at higher loading rate. Abstract: Slaughterhouse wastes (SHW) are potentially very attractive substrates for biogas production. However, mono-digestion of these wastes creates great technological problems associated with the inhibitory effects of ammonia and fatty acids on methanogens as well as with the foaming in the digesters. In the following study, the co-digestion of slaughterhouse wastes with sewage sludge (SS) was undertaken. Batch and semi-continuous experiments were performed at 35 °C with municipal sewage sludge and pig SHW composed of meat tissue, intestines, bristles and post-flotation sludge. In batch assays, meat tissue and intestinal wastes gave the highest methane productions of 976 and 826 dm 3 /kg VS, respectively, whereas the methane yield from the sludge was only 370 dm 3 /kg VS. The co-digestion of sewage sludge with 50% SHW (weight basis) provided the methane yield exceeding 600 dm 3 /kg VS, which was more than twice as high as the methane production from sewage sludge alone. However, when the loading rate exceeded 4 kg VS/m 3  d, a slight inhibition of methanogenesis was observed, without affecting the digester stability. The experiments showed that the co-digestion of sewage sludge with large amount of slaughterhouse wastes is feasible, and the enhanced methane production does not affect the digester stability.